Cyber Diplomacy Framework for India: Lessons from Global Strategies and a Roadmap for the Future - Kishor, Samrat (Journal of Advanced Research in Electronics Engineering and Technology; Vol 12 No 1&2 (2025): Journal of Advanced Research in Electronics Engineering and Technology, 2025)
In an era where cyber threats are increasingly shaping international relations, cyber diplomacy has become a critical component of national security and foreign policy. This research paper explores the cyber diplomacy frameworks adopted by developed nations, including the United States, the European Union, and Australia, to understand their key components, strategic priorities, and operational mechanisms. It then examines India’s current approach to cyber diplomacy, identifying gaps and opportunities for enhancement. Through a comparative analysis, the paper proposes a structured cyber diplomacy framework tailored for India, integrating elements of international cooperation, capacity building, legal frameworks, and public-private partnerships. The study underscores the necessity of a proactive and multilateral approach to safeguard national cyber interests while fostering global digital trust and stability. The result provide to policy recommendations that can guide India in formulating a robust and adaptive cyber diplomacy strategy.